A Double Machine Learning Approach to Estimate the Effects of Musical Practice on Student's Skills - Michael C. Knaus (Institute of Labor Economics (IZA), 2018)
This study investigates the dose-response effects of making music on youth development. Identification is based on the conditional independence assumption and estimation is implemented using a recent double machine learning estimator. The study proposes solutions to two highly practically relevant questions that arise for these new methods: (i) How to investigate sensitivity of estimates to tuning parameter choices in the machine learning part? (ii) How to assess covariate balancing in high-dimensional settings? The results show that improvements in objectively measured cognitive skills require at least medium intensity, while improvements in school grades are already observed for low intensity of practice.
Keywords: J24; Z11; C21; C31; 330; double machine learning; extracurricular activities; music; cognitive and non-cognitive skills; youth development